Cochlear implantation for severe mixed hearing loss caused by Treacher Collins syndrome: Case report - Ostojić-Zeljković Sanja; Nikolić Mina; Đoković Sanja (Vojnosanitetski Pregled, 2024)
Introduction. Treacher Collins syndrome (TCS) is a rare genetic condition characterized by typical head and neck malformations occurring in 1:50,000 newborns. Permanent conductive or mixed hearing loss of various degrees is diagnosed in 50% of individuals with TCS. A prerequisite for speech and language development in children with permanent mixed hearing impairment is the application of one of the bone conduction hearing aids. Choosing an adequate hearing aid in this case depends primarily on the degree of hearing impairment and the type of ear malformation. Case report. We present a female patient with multiple genetic malformations due to TCS. The patient was, immediately after birth, referred for audiological evaluation because of considerable ear and face malformations. Using a hearing test battery, permanent mixed, predominantly conductive, bilateral hearing loss of severe degree was diagnosed. The use of bone conduction hearing aids (including the Vibrant® Soundbridge middle ear implant) in the patient did not give the expected results – sufficient amplification for adequate speech and language development. Only after cochlear implantation at the age of nine did the patient’s hearing threshold stabilize and her communication and academic potential develop to full capacity. Conclusion. If a middle ear implant is not sufficient for adequate amplification, cochlear implantation should be considered as an appropriate solution for treating severe permanent mixed hearing impairment in patients with TCS.